Bosentan treatment for pulmonary arterial hypertension related to connective tissue disease: a subgroup analysis of the pivotal clinical trials and their open-label extensions. Issue 10 (22nd June 2006) - Denton, C P; Humbert, M; Rubin, L; Black, C M
Abstract : Background: Endothelin-1 is considered to be a central pathogenic factor in connective tissue diseases (CTDs) such as systemic sclerosis (SSc), leading to vasoconstriction, fibrosis, hypertrophy and inflammation. A frequent complication of CTD is pulmonary arterial hypertension (PAH), which has a major effect on functioning and quality of life, and is associated with a particularly poor prognosis. Objective: To present a subgroup analysis that summarises experiences from the pivotal studies and their open-label extensions with the oral dual endothelin-1 receptor antagonist bosentan in patients with PAH and CTD, mostly SSc and lupus erythematosus. Methods: 66 patients with PAH secondary to CTD, in World Health Organization functional class III or IV, were randomised to two double-blind, placebo-controlled studies and followed up for 12 and 16 weeks, respectively. The primary end point was change in exercise capacity, assessed using the 6-min walk test. In both studies and their extensions, survival was assessed from start of treatment to death or data cut-off and analysed as Kaplan–Meier estimates. Results: 44 patients with PAH secondary to CTD who were treated with bosentan were stable in 6-min walk distance at the end of the study (+19.5 m, 95% confidence interval (CI) −3.2 to 42.2), whereas patients treated with placebo deteriorated (−2.6 m, 95% CI −54.0 to 48.7). 64 patients subsequently received bosentan in an open-label long-term extension study. Mean (standard deviation (SD)) exposure to bosentan was 1.6 (0.9) years, and duration of observation was 1.8 (0.8) years. 8 (16%) patients received epoprostenol as add-on treatment and 7 (14%) after discontinuation of bosentan. Survival in those receiving bosentan was 85.9% after 1 year and 73.4% after 2 years. Conclusion: Short-term bosentan treatment in a subgroup of patients with PAH secondary to CTD seems to have a favourable effect compared with placebo. The long-term follow-up of these patients suggests that first-line bosentan, with the subsequent addition of other PAH treatments if required, is safe for long-term treatment and may have a positive effect on outcome.